TINGKAT KEPUASAN PASIEN UMUM DAN BPJS TERHADAP PELAYANAN KEFARMASIAN DI APOTEK CAHAYA HUSADA I CILACAP - AGUS SETIA PERMANA, DENIH (Gamma Publishing, 2023)
The quality of health services is services that can cause satisfaction to every patient where the procedures for its administration are in accordance with established standards and codes of ethics. This study aims to determine the level of general patient satisfaction and BPJS on the quality of pharmacy services at Cahaya Husada Pharmacy I Cilacap based on five dimensions of service quality, namely Realibility, Responsiveness, Assurance, Empathy, and Tangible, and Tangible. Physical proof). The results obtained are on the dimensions of reliability (0.08) in general patients and (0.13) in BPJS patients with satisfied classification, responsiveness (0.1) in general patients and (0.15) in BPJS patients with satisfied classification, guarantee (0.16) in general patients (0.02) in BPJS patients with satisfied classification, attention (0.06) in general patients and (0.04) in BPJS patients with satisfied classification and on physical evidence (0.08 ) in general patients and (0.06) in BPJS patients with satisfied classification. In conclusion, the quality of services received by general patients and BPJS patients are satisfied.